Thermally assisted semiconductor-like to insulator transition in gold-poly(methyl methacrylate) nanocomposites - Abyaneh, Majid Kazemian; Pasricha, Renu; Gosavi, S. W.; Kulkarni, S. K. (Nanotechnology, 2006)
Gold-polymethylmethacrylate ( PMMA) nanocomposites were fabricated by mixing gold nanoparticles capped with oleylamine in polymethylmethacrylate. The samples were analysed using UV-vis absorption spectroscopy, transmission electron microscopy, small angle x-ray scattering, Fourier transform infrared spectrometry ( FTIR) and x-ray photoelectron spectroscopy ( XPS). Electrical resistivity of nanocomposite samples was measured by a four-probe technique in the 70-300 K range. The nanocomposites showed a transition with an onset at similar to 160-165 K. They exhibited a semiconductor-like conductivity at higher temperatures and nearly temperature independent conductivity at lower temperatures. The interfacial interaction of Au nanoparticles and PMMA polymer is investigated using FTIR and XPS. A ligand-exchange process occurs when capped gold nanoparticles are incorporated in PMMA polymer.